Imitation, Collaboration, and Their Interaction Among Western and Indigenous Australian Preschool Children. Issue 3 (May 2016) - Nielsen, Mark; Mushin, Ilana; Tomaselli, Keyan; Whiten, Andrew
Abstract : This study explored how overimitation and collaboration interact in 3‐ to 6‐year‐old children in Westernized ( N  = 48 in Experiment 1; N  = 26 in Experiment 2) and Indigenous Australian communities ( N  = 26 in Experiment 2). Whether working in pairs or on their own rates of overimitation did not differ. However, when the causal functions of modeled actions were unclear, the Indigenous Australian children collaborated at enhanced rates compared to the Western children. When the causal role of witnessed actions was identifiable, collaboration rates were correlated with production of causally unnecessary actions, but in the Indigenous Australian children only. This study highlights how children employ imitation and collaboration when acquiring new skills and how the latter can be influenced by task structure and cultural background.